ISLAMIC APPROACHES TO THE ENVIRONMENTAL PRESERVATION: A SYSTEMATIC LITERATURE REVIEW - Zulkifli; Nuryaman; Hafidhoh (UIN Raden Mas Said Surakarta, 2023)
This study aims to investigate and review the Islamic perspective on the environment, identify Islamic approaches to preserve the environment and examine the effect of the Islamic approach in the empirical reality of the Muslim population. Based on a Systematic Literature Review of journal articles from the Scopus, the review results of 23 articles generated the Islamic perspective on the environment, namely the harmonious relationship of humans and the environment, the caliph’s role, the expression of faith and sharia obligations, and Islamic ethics. In preserving the environment, Islam proposes a theological approach, ethics and Sufism, Islamic law, comparative religion, educational, communication, philosophical, and social movement approaches. The review also found that while most studies demonstrate the positive effect of increasing Islamic environmental awareness, attitude, and actions, the two reveal an ineffective role of the Islamic environmental project and Islamic countries because environmental problems are subject to economic and political considerations. Future research should focus on explaining the diverse Islamic environmental perspectives and practices across different regions and cultures, fostering interdisciplinary collaboration among scholars to provide a comprehensive understanding of the topic.